2020
DOI: 10.1038/s41598-020-75756-5
|View full text |Cite
|
Sign up to set email alerts
|

HIFα independent mechanisms in renal carcinoma cells modulate divergent outcomes in fibronectin assembly mediated by hypoxia and CoCl2

Abstract: Fibronectin (FN) is a core matrix protein that assembles to form a dynamic cellular scaffold, frequently perturbed during oncogenic transformation. Tumor hypoxia, characterized by low oxygen concentrations in the microenvironment of most solid tumors has been shown to accelerate FN assembly in fibroblasts and cancer-associated fibroblasts, cell types that produce abundant amounts of FN protein. Nevertheless, FN matrix regulation in epithelial cancer cells during hypoxia remains less well defined. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
(54 reference statements)
3
6
0
Order By: Relevance
“…The decrease in FN fibrils in response to hypoxia was further confirmed in the three cell lines by immunolabelling FN ( Figure S1A). In accordance with our observations and from previous studies in renal epithelial cells, [27][28][29][30] we observed a two-fold increase in total FN protein in response to hypoxia indicating that the decrease in FN fibrils ( Figures 1A and S1A) is unlikely to be due to insufficient protein ( Figure 1C,D). Increased levels of HIF-1α and HIF-2α confirmed hypoxia response in these cell lines ( Figures 1E and S1B).…”
Section: Hypoxia Reduces Fn Fibrils In Untransformed and Transformesupporting
confidence: 93%
See 3 more Smart Citations
“…The decrease in FN fibrils in response to hypoxia was further confirmed in the three cell lines by immunolabelling FN ( Figure S1A). In accordance with our observations and from previous studies in renal epithelial cells, [27][28][29][30] we observed a two-fold increase in total FN protein in response to hypoxia indicating that the decrease in FN fibrils ( Figures 1A and S1A) is unlikely to be due to insufficient protein ( Figure 1C,D). Increased levels of HIF-1α and HIF-2α confirmed hypoxia response in these cell lines ( Figures 1E and S1B).…”
Section: Hypoxia Reduces Fn Fibrils In Untransformed and Transformesupporting
confidence: 93%
“…This reasoning has been corroborated by findings in breast cell lines, demonstrating that although FUD treatment did not alter chemotactic migration of MCF10A cells, FUD decreased the TGF‐β1‐mediated cell migration 43 . Although we and others have previously shown that renal epithelial cells exposed to hypoxia disassemble the FN matrix, perhaps involving cell trafficking of the FN protein, it is still unclear how this process of FN disassembly is initiated or mediated 28 . For this reason, we were unable to target a specific mechanistic process to reverse fibril disassembly.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…It has a complex mechanism which is still not clear and may be related to the MAPK signaling pathway, phosphatidylinositol signaling pathway and cytokine-cytokine receptor pathway [40,41]. Many studies have shown that cells migrate faster under hypoxia than normoxia, including mesenchymal stem cells and carcinoma cells [42][43][44]. Magdaleno et al [43] compared the migration of renal carcinoma cells under hypoxia and CoCl 2 and found that physical hypoxia promoted migration but CoCl 2 failed to achieve similar effect.…”
Section: Cell Migrationmentioning
confidence: 99%